Enhanced signalling provisioning for UAV‐enabled MEC: A GWFRFT‐based energy‐spreading transmission approach. Issue 15 (1st September 2020) - Li, Chengfang; Fang, Xiaojie; Zhou, Xiaokang; Mei, Lin; Sha, Xuejun
Abstract : With the high mobility, flexibility and manoeuvrability, unmanned aerial vehicles (UAVs)‐enabled mobile edge computing (MEC) plays an important role in many applications that lack of available terrestrial infrastructures, such as disaster response, emergency relief and military scenarios. However, the high mobility of UAVs may severely degrade the implementation of UAV‐enabled MEC in computation‐intensive or delay‐sensitive scenarios from a physical layer signalling perspective, e.g. frequency selective fading effect caused by the low altitude and low elevation angle routes of UAVs. In this study, a generalised weighted‐type fractional Fourier transform (GWFRFT) based signal energy‐spreading transmission (EST) scheme is proposed for signalling and quality of service (QoS) provisioning for UAV‐enabled MEC. In the proposed scheme, the communication signal energy is redistributed evenly at the time‐frequency plane to enhance the robustness of UAV communications against the severe fading channels. The signalling provisioning mechanism of the GWFRFT‐EST scheme is analysed and simulated under poor air‐to‐ground channels with low Rician K ‐factor. Simulation results show that the proposed method greatly improves the bit error rate performance with a negligible computational complexity increase.